Предмет: Алгебра,
автор: ibelkharoev
Докажите тождество (m+n)*(m^2-mn+n^2)=m^3+n^3
Ответы
Автор ответа:
0
Докажите тождество (m+n)*(m² - mn+n²)=m³+n³ .
* * * просто открываем скобки * * *
(m+n)*(m² - mn+n²) =m³-m²n+mn² +nm² -mn²+n³ = m³+n³ .
* * * или обратном порядке * * *
Используем тождество : (m+n)³ =m³+3m²n+3mn²+n³ = m³+n³ +3mn(m+n) ⇒
m³+n³ =(m+n)³ - 3mn(m+n) =(m+n)( ((m+n)² - 3mn) =
(m+n)( (m²+2mn+n² - 3mn) = m+n)( (m² mn+n²) .
* * * просто открываем скобки * * *
(m+n)*(m² - mn+n²) =m³-m²n+mn² +nm² -mn²+n³ = m³+n³ .
* * * или обратном порядке * * *
Используем тождество : (m+n)³ =m³+3m²n+3mn²+n³ = m³+n³ +3mn(m+n) ⇒
m³+n³ =(m+n)³ - 3mn(m+n) =(m+n)( ((m+n)² - 3mn) =
(m+n)( (m²+2mn+n² - 3mn) = m+n)( (m² mn+n²) .
Похожие вопросы
Предмет: Русский язык,
автор: DaniiarBaizhanov
Предмет: История,
автор: vikachika19
Предмет: Другие предметы,
автор: uskamaksim
Предмет: Обществознание,
автор: Ninasiukova
Предмет: Биология,
автор: Аноним